ANALYZING INVENTORY CONTROL THROUGH THE EOQ METHOD TO IMPROVE PURCHASING EFFECTIVENESS AT MEXSHAMALL - Malinda, Agia Salsa; Ridwan, Rizky; Khodijah, Amalia Siti (Distribusi - Journal of Management and Business, 2025)
This study adds originality by looking at the Economic Order Quantity 1 (EOQ) method at Mexshamall operations, a Muslim fashion retail business that deals with difficulties of excessive inventory, ineffective procurement, and cash flow interruptions. The study's goal is to assess the effectiveness of EOQ 8 in managing inventory and boosting buying efficiency in comparison to the firm's conventional methods. The descriptive quantitative methodology used primary data from interviews and observation, as well as secondary data such as purchase reports, ordering costs, holding costs, and demand data. The study compared the company's current procedures to the best order quantity, safety stock, reorder point, and total inventory cost (TIC). The empirical data show that EOQ implementation results in an ideal order size of 103,638 pieces per order, with a frequency of 24 orders annually, safety. TIC declined from IDR 22,620,930 to IDR 18,240,256 per year, saving about IDR 7,661 units, with a reorder threshold of 26,940 units. IDR 4,380,674 and the frequency of purchases exhibited a notable decline, reducing from 48 to 24 instances. In addition, EOQ was shown to increase liquidity, reduce credit risk, and optimize the use of working capital. The implications suggest that EOQ implementation can be rolled out gradually by organizations, fostering data-driven decision-making, improving inventory management, and providing financial rewards. Mexshamall and other small and medium-sized enterprises with comparatively cheap implementation expenses.